Evaluation of CUDA GPU architecture as H.264 intra coding acceleration engine - Husemann, Ronaldo; Roesler, Valter; Lima, José Valdeni de; Gobbi, Marco Antonio (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2013: Proceedings of the 19th Brazilian Symposium on Multimedia and the Web, 2013)
Currently the high computational complexity makes it very difficult to produce a whole high definition real-time H.264 encoder solution, for conventional personal computer platform, based only on single-threaded software implementation. Considering that, the current paper analyses the potential of using modern general purpose graphical processing technologies, such as NVIDIA CUDA ® platform, as acceleration engines to improve the overall performance of a computer based H.264 intra video encoder. Performed experiments allowed discriminating the real gains when replacing a CPU based only solution by a GPU solution identifying some practical bottlenecks related with that technology. The most efficient proposal was finally compared with the original H.264/AVC reference code and the optimized x264 open source library codec, registering significant performance gains (in same cases higher than 7.6x).